Three‐Dimensional Hybrid Simulation of Viscous‐Like Processes at Saturn's Magnetopause Boundary - P. A. Delamere; B. Burkholder; X. Ma (Geophysical Research Letters, 2018)
Abstract Saturn's magnetosheath flows exhibit significant dawn/dusk asymmetry. The dawnside flows are reduced from expectation, suggesting significant momentum transport through the magnetopause boundary where the flow shear is maximized. It has been suggested that the solar wind interaction with the giant magnetospheres is, in fact, dominated by a viscous‐like interaction governed by the Kelvin‐Helmholtz instability. In three dimensions, the Kelvin‐Helmholtz instability can generate small‐scale and intermittent magnetic reconnection due, in part, to a twisted magnetic field topology. The net result is a field line threading of the magnetopause boundary and the generation of Maxwell shear stresses. Here we present three‐dimensional hybrid simulations (kinetic ions and massless fluid electrons) of conditions similar to Saturn's dawnside magnetopause boundary to quantify the viscous‐like, tangential drag. Using model‐determined momentum fluxes, we estimate the effect on dawnside sheath flows and find very good agreement with observations.